Ultrasound therapy and stretching of wrist extensors on pain, motion and functional impairment of the wrist in patients with carpal tunnel syndrome - Sari, Cindi Permata; Herawati, Isnaini (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Carpal tunnel syndrome (CPT) is a medical situation when there is pressure on the median nerve, where the wrist is located, which makes parasthesias, numbness and weak hand muscles. Several interventions can be done to overcome patient problems, one of which is physiotherapy. This study is intended to identify in-depth information related to the effectiveness of ultrasound therapy along with wrist stretching to reduce pain and make functional improvements in the wrists of patients with CTS. Purpose: To determine the benefits of ultrasound therapy also wrist stretching for patients with CTS. Method: This quasi-experimental study employs a pre-test and post-test design with a control group of ten respondents who have had CTS. This study employs the DASH questionnaire, the VAS, and a goneometer to measure joint mobility area. Wilcoxon and Mann-Whitney tests used to analyze the data. Results: It was found that, motion pain decreased, joint motion area increased, and increased functional potential after intervention. The impact varied between group 1 and group 2 (p<0.05). However, in compressive pain and silent pain, the value of p>0.05 was found, so there was no difference in effect between the 2 groups, but group 2 had more changes than group 1. Conclusion: Ultrasound therapy and wrist stretching were shown to result in decreased pain, enhanced functional routine, also increased joint range of motion.